To blend or not to blend?! That’s the e-learning question! - Gil, Henrique (2009)
This paper aims to discuss and reflect about the importance of blended learning. Today blended learning became very popular but it is important find the best ways and the best types to deliver and ”consume ”it. It is common recognize blended learning as a mix of media and delivery. However there is very important to find out the “right mix” because it is known that different problems need different solutions. When we talk about higher education we deal with adults and we assume that students want and need to learn just enough to become more effective at their future jobs. The so called science of how to teach through the internet is still being development and in this paper is discussed the”evolution” of e-learning towards blended learning… But we assumed that every successful e-learning will become a blended learning course… The problem is to know and if we choose the «right mix«. This ”mix” should promote at least three different dimensions: thinking less about delivering instruction and more about producing learning, reaching out to students through distance education technologies, and promoting a strong sense of community among learners. In this paper some models were reflected by taking in account the main reason of their choice as well as the way to put them in practice.